INTEGRATIVE GENERALIZATION OF FORMS INTERACTIVE TEACHING METHODS (Pedagogy of Higher and Secondary Education, 2007)
This article considers from and content interactively method theaching of repairing future teachers. The author of the analyses the condition effect interactively method studies.